The Emotional Intelligence of Managers and Its Valuation - Pavlovska Liudmyla D.; Kaschuck Kateryna M. (Bìznes Inform, 2020)
The article is concerned with researching the role of emotional intelligence in the activities of managers. The authors carried out a study, which consisted of two stages. In the first stage, with the help of the methodology of scientists of the Rotterdam Emotional Intelligence Scale, the level of formedness of emotional intelligence was diagnosed in a group of magistrands studying at the educational institutions of the city of Zhytomyr in the specialty of «Management». In the second stage, by interviewing experts – the directors and managers of enterprises in the city of Zhytomyr – their opinion on the role of emotional intelligence in management activities is researched. According to the results of diagnosing the magistrands, the highest indicator has the identification of their own emotions, the lowest has the use of emotions to achieve the goal, which reflects the insufficient formedness of emotional competence in students in general. The results of the survey of experts at the enterprises showed that they highly valuate the role of emotional intelligence in their activities. At the same time, they are not fully aware of the difference between emotional intelligence and other types of intellectual abilities, as well as the role of its individual structural elements. According to their valuation, emotional intelligence is necessary in solving a wide range of professional tasks, most of which involve the performance of basic functional responsibilities: recruitment, training and motivation of staff. Comparison of the results of the diagnosis of the level of formedness of emotional intelligence in magistrands and the valuation of its role in management practice reveals a significant discrepancy between them. There are two possible explanations for this gap: 1) the high valuation by practitioners of the role of emotional intelligence is based on traditional perceptions of the content and means of management activity; 2) the average level of formedness of emotional intelligence among students is the result of its insufficient development through curricula. The results can be used in professional counseling, in the selection and training of managers.